Immunophenotypic Characterisation And Evaluation Of Minimal Residual Disease (Mrd) In Acute Leukaemia Patients In Sarawak By Flow Cytometry - Mohamad Razif, Othman (Universiti Malaysia Sarawak (UNIMAS), 2013)
Leukaemia is a malignant disease of the bone marrow and blood which usually affect children and adults. Minimal residual disease (MRD) is the definition given to a small numbers of leukaemic cells that remain in the patient when the patient is in remission, and a known cause of relapse in cancer and leukaemia. Using immunophenotypic multiparametric flow cytometry, sequential studies (diagnosis and follow-up) of the characterisation of the leukaemic blast and the association between the clinical parameters of 147 acute myeloid leukaemia (AML) patients and 122 acute lymphoblastic leukaemia (ALL) were investigated. Patients diagnosed with acute leukaemia were recruited from hospitals all over Sarawak within the duration of 3 years, from 2007 until 2010. Patients were studied at diagnosis with a panel of monoclonal antibodies in 3- and 4-colour antibody combinations for detections of common, aberrant or uncommon phenotypic features. Using the patient’s immunophenotypic features during diagnosis, the identification of residual leukaemic cells were made possible after completion of induction chemotherapy and the frequency of antigen expression was determined for minimal residual detection. Other clinical data such as haemoglobin level, lymph node enlargement, liver, splenomegaly, platelet and white blood count were also analysed. The odds ratio between MRD and the relevant parameters involved was also calculated with statistical software. The data were analysed statistically and p value < 0.05 is considered as statistically significant. In the AML cases, female childhood patients were found to have higher total white count compared to males (p =0.008). Immunophenotypic results also showed similar expressions between childhood and adult group with high expression of CD33, CD13 and aberrant marker such as CD19, and may be established as diagnosis standard markers. In the ALL cases, for the Malay/Melanau ethnic group, more adult males were diagnosed with B-ALL compared to adult females (p=0.043). Antigen expressions for both childhood and adult groups were similar to previous studies, with CyCD79a, CD19, CD22 for B-ALL, while CD7 and CyCD3 for T-ALL, thus suggesting the antibody panels used may be established as diagnostic markers. For the MRD analysis, only 28 AML cases (19.0%) were analysed for MRD and no clinical and immunophenotypic parameter was significantly related with MRD outcome. Multiple logistic regression (MLR) analysis for AML was also not significant. As for ALL, 77 cases (64.2%) were studied for MRD. It was found that low haemoglobin level was significantly associated with positive MRD (p<0.001*). In MLR analysis, haemoglobin level and splenomegaly were found to be significantly associated with MRD positivity, with odd risks of 1.68 and 37.98 respectively. Overall, from the study it can be concluded that clinical parameters and immunophenotypic expressions could be used as a predictive factors in MRD outcome. This study could be improved by a greater effort to coordinate leukaemia patients’ treatment and follow up in Sarawak. A more comprehensive study regarding MRD in acute leukaemia patients is therefore recommended in order to provide the health providers more concrete data about the prognostic/predictive factors that may influence the disease outcome, and eventually assist in the future treatment and management of acute leukaemia in Sarawak.